MODEL INTEGRATED TOTAL QUALITY MANAGEMENT DI SEKOLAH BERBASIS PESANTREN - Ahmad Yusuf (Tadbir: Jurnal Manajemen Pendidikan Islam, 2021)
This article aims to describe how the Integrated Total Quality Management (ITQM) model in Pesantren-Based Schools. By using the Research and Development (R&D) research model within the framework of a qualitative approach. The result of this research is that the Integrated Total Quality Management (ITQM) model in Pesantren-Based Schools can only be built on the basis of a commitment among the management system of the Pesantren (Islamic Boarding School), the Foundation and the school having an alignment of vision, mission and goals. The three managerial processes persistently to carry out quality planning, quality organizing, quality actuating and quality controlling in every management process and well coordinated with each other so that there is no overlapping of policies and programs. The third commitment of management is always to seek opportunities for more efficient and effective integrated management in improving the quality of education and focusing on customer satisfaction and continuous improvement.